2017
DOI: 10.1111/flan.12263
|View full text |Cite
|
Sign up to set email alerts
|

Developing L2 Pragmatic Competence in Mandarin Chinese: Sequential Realization of Requests

Abstract: The present study explored the development of second language (L2) Chinese learners' ability to negotiate requests in interactions. It investigated the effect of proficiency on learners' use of request strategies and internal modifications and on their sequential realization of requests in L2 Chinese. Twenty‐four American English learners of L2 Mandarin Chinese at three different proficiency levels completed a three‐scenario role‐play task. The scenarios were kept low in imposition and social distance but vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The popularity of 'downtoners/understaters' and 'politeness markers' in the Chinese requests mirrors what has been previously found. For example, Su and Ren (2017) found that interrogatives and understaters were two popular modifiers in Chinese requests, followed by politeness markers. These three strategies were also the three most frequently used internal modifiers in the Chinese requests in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of 'downtoners/understaters' and 'politeness markers' in the Chinese requests mirrors what has been previously found. For example, Su and Ren (2017) found that interrogatives and understaters were two popular modifiers in Chinese requests, followed by politeness markers. These three strategies were also the three most frequently used internal modifiers in the Chinese requests in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Interactional research on L2 Mandarin remains rare. A small number of studies have investigated aspects of interaction, such as sequential organi-zation of request (Su & Ren, 2017) and discourse markers (Tsai & Chu, 2017), but no interactional studies of L2 Chinese refusals exist.…”
Section: Refusals In Mandarin Chinese L1 and L2mentioning
confidence: 99%
“…Authors from 48 countries contributed to the publication. The most productive countries (at least 10 articles) as the first author were the United States (211), England (45), China (34), Germany (33), Canada (33), Netherlands (20), Australia (19), France (19), Italy (15), Sweden (13), Belgium (12), Japan (12), and Korea (10), suggesting that the topics relevant to the pragmatic and usage-based language learning were interested by research groups with expertise in linguistics and/or psychology, and the languages of interest were more various. Besides the Indo-European languages such as English, German, French, and Italian, the East-Asian languages, in particular, Chinese, Japanese, and Korean, are the popular languages of research.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…The keywords that appeared at least five times among target publications in the topic of psycholinguistics and pragmatic and usage-based language processing highlighted the following related themes [Language (17), Comprehension (11), Psycholinguistics (10), Speech (8), Speakers (7), Acquisition (6), Information (5), Context (5), and Perception (5)] and methodology [Eye-movements (5) and Children (5)]. In the topic of usage-based and pragmatic language learning, the keywords that occurred at least 10 times among target publications represented the themes highlighting Second Language Acquisition (76) and L2 Acquisition (15), Bilingualism (56), Language Acquisition (23), Spanish (20), Pragmatics (17), Study Abroad (15), Language, (14), Working Memory (14), Second Language (13), English (13), Vocabulary (13), Second Language Learning (12), German (10), Interlanguage Pragmatics (10), and fMRI (10). The comparison of the keywords between these two topics clearly indicates a distinct trend of research interest and methodology of use in the field psycholinguistics and the field of second-language acquisition studies.…”
Section: Bibliometric Analysismentioning
confidence: 99%
See 1 more Smart Citation